Avifauna del Parque Nacional Pre-Delta, Entre Ríos, Argentina - Alonso, Julian Mariano; Ronchi Virgolini, Ana Laura
Between February 2005 and November 2006, we made systematic surveys of birds in the Pre-Delta National Park, Entre Ríos, north-east Argentina, as part of a study designed to provide basic data for future use in the conservation and management of this protected area. We discovered relatively high ornithological richness, recording 238 bird species (117 Passeriformes and 121 NonPasseriformes), belonging to 18 orders and 48 families, and representing 70% of the bird species known from Entre Ríos and 24% of those known from the whole country. Among threatened species and/or those of particular interest at national and global levels were: Muscovy Duck Cairina moschata, Jabiru Jabiru mycteria, Osprey Pandion haliaetus, Great Black Hawk Buteogallus urubitinga, Swainson’s Hawk Buteo swainsoni, Peregrine Falcon Falco peregrinus, Tawny-bellied Seedeater Sporophila hypoxantha, Rufous-rumped Seedeater S. hypochroma, Marsh Seedeater S. palustris and Scarlet-headed Blackbird Amblyramphus holosericeus Fil: Alonso, Julian Mariano. Parque Nacional Pre-Delta; Argentina Fil: Ronchi Virgolini, Ana Laura. Provincia de Entre Ríos. Centro de Investigaciones Científicas y Transferencia de Tecnología a la Producción. Universidad Autónoma de Entre Ríos. Centro de Investigaciones Científicas y Transferencia de Tecnología a la Producción. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Santa Fe. Centro de Investigaciones Científicas y Transferencia de Tecnología a la Producción; Argentina